2015
DOI: 10.1016/j.mcn.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of secreted neuropeptides and catecholamines illustrate similarities and differences in response to stimulation by distinct secretagogues

Abstract: The goal of this study was to define profiles of secreted neuropeptide and catecholamine neurotransmitters that undergo co-release from sympathoadrenal chromaffin cells upon stimulation by distinct secretagogues. Chromaffin cells of the adrenal medulla participate in the dynamic responses to stress, especially that of ‘fight and flight’, and, thus, analyses of the co-release of multiple neurotransmitters is necessary to gain knowledge of how the stress response regulates cell-cell communication among physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Another interesting result was that AD and NA levels were 1000 times higher than those found for neuropeptides, especially MENK. Likewise, Podvin and co‐workers found the same proportions in large dense core secretory vesicles of BCCs . Winkler et al found a 0.4 M catecholamine concentration in adrenal large dense‐core vesicles, in contrast to our findings in BCCs (0.95 × 10 −3 M cell −1 for AD and 0.45 × 10 −3 M cell −1 for NA) if the pertinent conversion is made from our data in µg ml −1 (5 × 10 6 cells) Figure A.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Another interesting result was that AD and NA levels were 1000 times higher than those found for neuropeptides, especially MENK. Likewise, Podvin and co‐workers found the same proportions in large dense core secretory vesicles of BCCs . Winkler et al found a 0.4 M catecholamine concentration in adrenal large dense‐core vesicles, in contrast to our findings in BCCs (0.95 × 10 −3 M cell −1 for AD and 0.45 × 10 −3 M cell −1 for NA) if the pertinent conversion is made from our data in µg ml −1 (5 × 10 6 cells) Figure A.…”
Section: Resultssupporting
confidence: 59%
“…NA, AD and DA levels have also been determined using electrochemical detection, and NA, AD, DA and 5‐HT have been studied using HPLC‐MS in BCCs . Gu et al analyzed catecholamines and their metabolites in an adrenal gland sample, and Podvin et al determined the vesicular content of neuropeptides and catecholamines in BCCs by radioimmunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…This nonapeptide acts on smooth muscles with contractions or relaxations. In the neuronal cells of vertebrates, bradykinin evokes a release of neuropeptides (galanin, neuropeptide Y, and vasoactive intestinal peptide) and catecholamines (dopamine, norepinephrine, and epinephrine) by depolarizing nerve terminals [ 25 , 103 ].…”
Section: Venom Peptidesmentioning
confidence: 99%
“…Another set of genes, encoding several neuropeptides (including PENK, NPY and galanin) which are co-released with catecholamines in neuronal activity-dependent manner ([ 44 ]), were also significantly increased in the 2RH0 group ( Table 1 , Fig 6A , S1 Table ). Our data are consistent with previously reported long lasting overexpression of several neuropeptides in response to stress (including acute hypoglycemia, [ 45 ], [ 46 ], [ 47 ]).…”
Section: Discussionmentioning
confidence: 99%